Extreme poverty and marginality in Bangladesh: Review of extreme poverty focused innovative programmes - Ali Zulfiqar; Mustafa K. Mujeri; Ahmed Badrun Nessa (University of Bonn, Center for Development Research (ZEF), 2014)
Bangladesh has achieved notable progress in poverty reduction including reduction in extreme poverty since 1990. Still a good proportion of the people in the country are living in extreme poverty and suffering from various kinds of deprivation and marginalization. It is therefore important to look into the factors that are responsible for deprivation and marginalization and address them appropriately in order to help the extreme poor and the marginalized communities to overcome poverty. The majority of the anti-poverty programmes being implemented in the country suffer from a number of limitations, especially, with respect to addressing the needs and demands of the extreme poor groups and the marginalized communities. Given this context, it is critically important to have dedicated and innovative programmes to cater the needs of the extreme and marginalized people living in different areas in the country. Some innovations have already begun in respect of addressing extreme poverty and marginality in the country. This review of some of these programmes reveals that they have been successful in reaching and meeting the needs of the extreme poor households. However, given the fact that there are still a large number of extreme poor households who need support of this kind, efforts should be intensified to reach them and to bring them out of extreme poverty within the shortest possible time.
Keywords: I3; I30; I31; I38; 330; Extreme Poverty; Marginality and Innovative Program